Beyond atrial septal defect closure, it is time to start seriously considering closing ventricular septal defects with devices. (January 2020) - Thompson, Jim
Abstract : Purpose of review: The purpose of this review is to discuss the history and current state of transcutaneous device closure of ventricular septal defects. Recent findings: Newer devices and techniques have expanded the role of transcutaneous device closure of ventricular septal defects. Device closure of ventricular septal defects is a mainstay of therapy in many parts of the world. Device closure in smaller infants has relatively higher risks than larger infants and older children. The potential for the development of complete heart block remains a concern with this procedure. Summary: Transcutaneous device closure of ventricular septal defects is a safe alternative to surgical repair in many patients.